Content, speciation and in vitro bioaccessibility of trace elements in seaweeds and derived food products - da Silva Junior, Ediu Carlos; Babaahmadifooladi, Mehrnoosh; Folens, Karel; dos Reis, André Rodrigues [UNESP]; Guilherme, Luiz Roberto Guimarães; Van de Wiele, Tom; Jacxsens, Liesbeth; Du Laing, Gijs (Elsevier, 2023)
Seaweed products currently emerging in Europe are known to be potentially contaminated by toxic elements. The present study focused on the contents and bioaccessibility of trace elements in seaweed products available in Belgium. A total of 231 samples were collected in markets and As, Cd, Ni, Hg, Pb, I and Se concentrations were measured. Moreover, As speciation and the effect of a washing treatment on total concentrations of trace elements were studied. Bioaccessibility was assessed via in vitro simulation of the gastrointestinal digestion. A percentage of 85%, 39% and 4% of the samples exceed the concentration levels permitted for As, Cd and I respectively. Washing significantly reduced concentrations of all trace elements assessed. Speciation analysis identified a high percentage of inorganic As in hijiki. The average bioaccessibility in the small intestine was: As (52%) > Ni (35%) > Pb (27%) > Cd (20%). The population should seek practices such as washing to reduce the concentration and bioaccessibility of trace elements in seaweeds.
Keywords: Edible seaweeds; Food contamination; Gastrointestinal digestion; Speciation analysis; Toxic elements; Western europe